Web design structure with wordpress content management for sports centre booking system - Nor Sajidah Ab Ghani; Murizah Kassim; Aziati Husna Awang (Institute of Advanced Engineering and Science, 2020)
Sports center booking system need to be more systematic to increase its efficiency. The world wide web (WWW) had been a revolution and it has been utilized to be tools of automation in many applications, including managing booking and payment system in this area of services. However, existing system needs an ID booking to book the facilities at the court centre and does not delegate any confirmation to users on their booking. This paper aims at integrating stripe payment method by using the WordPress platform where it is one of the content management system (CMS) by using XAMPP. MySQL has been used to store the database while PHP and HTML have been designed to generate QR code. This system was designed based on some function needed for the new member, staffs, and students. The procedure is that the new members will register and pay their members fees. Existing student and staff will just need to sign in using their ID number. This system has provided a booking system which presented the availability of time and date as well as the payment for the new members. Upon booking and payment, email and QR code are given to the user after the confirmation booking by an administrator. The result shows the increase of efficiency after implementing the new features on the web system which shows 86.66% of increases in term of using the website to book the facilities at the sports centre from the existing system.